Enhanced osteogenic marker expression in alveolar bone via hydroxyapatite gypsum puger cassava starch scaffold: An in vivo study - Amiyatun Naini; Dessy Rachmawati; Zainul Cholid; Ardhianing Hardita; Afif Surya Adena; Siti Khaerunnisa (The Journal of Indian Prosthodontic Society)
Aim: To evaluate the effects of hydroxyapatite gypsum puger–cassava starch (HAGP-CS) scaffold on the number of osteoblasts and alkaline phosphatase (ALP) and osteocalcin (OCN) expression in the alveolar bone rat model. Settings and Design: In vivo study. Materials and Methods: Thirty-six Wistar rats were randomly divided into three groups: rat sockets were given a 1 mm × 1 mm × 1 mm HAGP scaffold, rat sockets were given a 1 mm × 1 mm × 1 mm HAGP-CS, and a control group (rat sockets were not given scaffold material). Following lower left molar extraction, scaffold materials were applied to the sockets. Assessments were conducted on days 7th, 14th, and 28th, with osteoblast counts determined via hematoxylin-eosin staining, and ALP and OCN expressions were analyzed using immunohistochemistry (IHC) staining. Statistical Analysis Used: Two-way analysis of variance and Tukey’s test. Results: A significant increase in osteoblast count was observed on day 28 (P = 0.001). In addition, significant differences were noted in ALP expression on day 7 (P = 0.030) and day 28 (P = 0.001), as well as in OCN expression on days 7 and 28 (P = 0.001) across the groups. Conclusions: Administering a HAGP-CS scaffold significantly enhances osteoblast proliferation and increases ALP and OCN expression in the alveolar bone rat model.